THE RELATIONSHIP BETWEEN ENDOTHELIAL FUNCTION AND MICROVASCULAR REMODELLING. (June 2018) - Masi, S.; Georgiopoulos, G.; Grassi, G.; Serravalle, G.L.; Savoia, C.; Taddei, S.; Rizzoni, D.; Virdis, A.
Abstract : Objective: Remodelling of small resistance vessels has been linked with cardiovascular outcomes and is facilitated by exposure to cardiovascular risk factors and endothelial dysfunction. Several studies have shown that endothelial dysfunction can provide additional information on the severity of vascular remodelling in large vessels. However, whether endothelial function can add additional information than common cardiovascular risk factor scores on the severity of remodelling indexes in small arteries remains unknown. We assessed the relationship between common cardiovascular risk scores and severity of microvascular remodelling as well as the influence of microvascular endothelial function on these relationships. Design and method: Small resistance arteries were isolated from biopsy of subcutaneous tissue obtained from laparoscopic procedures of 188 patients and used for micromyography experiments, where severity of microvascular remodelling was assessed by meadia:lumen ratio (M/L) and media cross-sectional area (MCSA), while endothelial-dependent vasodilation (EDD) was assessed by dose-response curves to acetylcholine. The Framingham and Heart Scores (FRS & HS) were calculated to assess the association between cardiovascular risk factors and severity of microvascular remodelling. Results: In a multivariable model including EDD, age, sex, smoking history, total cholesterol, BMI and hypertension, EDD (beta = −0.009, p < 0.001), and ageing (beta = 0.005, p = 0.033) were significantly associated with M/L ratio. A higher FRS was associated with a greater M/L ratio (beta = 0.086, p < 0.001) and MCSA (beta = 0.093, p = 0.020). Slightly weaker associations were obtained between HS vs M/L ratio (beta = 0.058, p = 0.018) and HS vs MCSA (beta = 0.066, p = 0.077). Neither the FRS, nor the HS showed significant association with M/L and MCSA when endothelial function was added to the models, while EDD remained strongly associated with both (p < 0.001 in both FRS and HS models). The association of EDD with M/L and MCSA was stronger in subjects with low compared to high cardiovascular risk at the FRS and HS (Figure 1). Figure. No caption available. Conclusions: The FRS seems to have a stronger relationship with parameters of microvascular remodelling than the HS. Endothelial function completely explains the association between FRS or HS with indexes of microvascular remodelling, representing the strongest predictor of microvascular remodelling, particularly in subjects at low risk of cardiovascular disease.